Chiwit thi thuk lamoet ruang lao kathoei thom di ying rak ying chai rak chai lae kotmai sitthi manutsayachon rawang prathet = Violated lives : narratives from LGBTIQs and international human rights law (Krung Thēp Mūnnithi Thīranāt Kānčhanaʻaksō̜n, 2011)
Narratives from homosexuals, gays, and lesbians in Thailand and international human rights law.
In Thai, with some articles in English.
UCWS-3280g donated by Hender Gercio - July 2013
UCWS-3281g donated by Ron de Vera & Nathan Caalim - September 2013
Keywords: Homosexuality -- Thailand; Gays -- Legal status, rights, etc. -- Thailand; Lesbians -- Legal status, rights, etc. -- Thailand; Human rights -- Thailand